Primary renal well-differentiated neuroendocrine tumors: report of six cases with an emphasis on the Ki-67 index and mitosis - Bohyun Kim; Han-Seong Kim; Kyung Chul Moon (BMC, 2019)
Abstract Background Primary renal well-differentiated neuroendocrine tumors (WDNETs) also called carcinoid and atypical carcinoid are extremely rare, and little is known about parameters that may predict prognosis at diagnosis. Methods Six cases of primary renal WDNET were collected. After reviewing slides stained with hematoxylin and eosin, proportions of each growth pattern were determined. Synaptophysin, chromogranin, CD56, and Ki-67 immunostaining and Ki-67 morphometric analysis were performed. Results Patients included three female and three males, mean age was 53.3 years. The mean tumor size was 4.5 cm, three cases were greater than 5 cm. At the time of initial surgery, lymph node and/or distant metastasis was confirmed in two cases. In a third case, no metastasis was initially found, but lymph node metastasis was identified during follow-up. The remaining three cases did not exhibit metastasis. Histopathologically, the renal WDNETs were primarily composed of ribbon-like and sheet-like growth patterns. Most of the tumors were diffusely positive for neuroendocrine markers. Mitotic count was high (≥2/10HPF) in cases with lymph node or distant metastasis but was low (< 2/10HPF) in non-metastatic cases. Furthermore, the Ki-67 index was also higher (≥3%) in the cases with metastases than in cases without metastasis. Conclusion Three out of the six primary renal WDNETs demonstrated aggressive behavior and exhibited increased mitotic counts and Ki-67 indices. These results suggest that mitosis and the Ki-67 index could be used as prognostic indicators for renal WDNET.